Dosimetric characterization of a microDiamond detector in clinical scanned carbon ion beams. Issue 4 (31st March 2015) - Marinelli, Marco; Prestopino, G.; Verona, C.; Verona‐Rinati, G.; Ciocca, M.; Mirandola, A.; Mairani, A.; Raffaele, L.; Magro, G.
Abstract : Purpose: To investigate for the first time the dosimetric properties of a new commercial synthetic diamond detector (PTW microDiamond) in high‐energy scanned clinical carbon ion beams generated by a synchrotron at the CNAO facility. Methods: The detector response was evaluated in a water phantom with actively scanned carbon ion beams ranging from 115 to 380 MeV/u (30–250 mm Bragg peak depth in water). Homogeneous square fields of 3 × 3 and 6 × 6 cm 2 were used. Short‐ and medium‐term (2 months) detector response stability, dependence on beam energy as well as ion type (carbon ions and protons), linearity with dose, and directional and dose‐rate dependence were investigated. The depth dose curve of a 280 MeV/u carbon ion beam, scanned over a 3 × 3 cm 2 area, was measured with the microDiamond detector and compared to that measured using a PTW Advanced Markus ionization chamber, and also simulated usingfluka Monte Carlo code. The detector response in two spread‐out‐Bragg‐peaks (SOBPs), respectively, centered at 9 and 21 cm depths in water and calculated using the treatment planning system (TPS) used at CNAO, was measured. Results: A negligible drift of detector sensitivity within the experimental session was seen, indicating that no detector preirradiation was needed. Short‐term response reproducibility around 1% (1 standard deviation) was found. Only 2% maximum variation of microDiamond sensitivity was observed among all the evaluated proton and carbon ion beam energies. The detector response showed a good linear behavior. Detector sensitivity was found to be dose‐rate independent, with a variation below 1.3% in the evaluated dose‐rate range. A very good agreement between measured and simulated Bragg curves with both microDiamond and Advanced Markus chamber was found, showing a negligible LET dependence of the tested detector. A depth dose curve was also measured by positioning the microDiamond with its main axis oriented orthogonally to the beam direction. A strong distortion in Bragg peak measurement was observed, confirming manufacturer recommendation on avoiding such configuration. Very good results were obtained for SOBP measurements, with a difference below 1% between measured and TPS‐calculated doses. The stability of detector sensitivity in the observation period was within the experimental uncertainty. Conclusions: Dosimetric characterization of a PTW microDiamond detector in high‐energy scanned carbon ion beams was performed. The results of the present study showed that this detector is suitable for dosimetry of clinical carbon ion beams, with a negligible LET and dose‐rate dependence.